2012
DOI: 10.1016/j.cellsig.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-dependent protein kinase is essential for hypoxia-mediated epithelial–mesenchymal transition, migration, and invasion in lung cancer cells

Abstract: Lung cancer is the leading cause of cancer-related death worldwide. Hypoxia is known to increase cancer cell migration and invasion. We have previously reported that hypoxia induces epithelial-mesenchymal transition (EMT) in lung cancer cells. However, it is unknown whether hypoxia promotes lung cancer cell migration and invasion via EMT and whether cyclic AMP (cAMP) dependent protein kinase (PKA) plays a role in this process. We found that hypoxia increased PKA activity and induced mRNA and protein expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 26 publications
6
62
0
Order By: Relevance
“…Numerous studies documented that the hypoxia microenvironment was able to enhance tumor progression [9,15]. A growing body of evidence demonstrated that there is a high correlation between hypoxia and lung cancer metastasis and poor prognosis [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies documented that the hypoxia microenvironment was able to enhance tumor progression [9,15]. A growing body of evidence demonstrated that there is a high correlation between hypoxia and lung cancer metastasis and poor prognosis [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that the hypoxia microenvironment promotes the growth and metastasis of lung cancer cells [8,9]. One-lung ventilation (OLV) is a standard anesthesia practice that was widely used in lung cancer resection surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent increase in cAMP levels induces the production of protein kinase A, which is essential for the hypoxia-mediated epithelialmesenchymal transition, as well as the migration and invasion of these tumorigenic cells in lung cancer. 28 Therefore, intrahepatic cholangiocarcinoma patient with this mutation may be investigated in a clinical trial for targeted therapy with protein kinase A inhibitors developed for that purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Alternate pathways for HSP27 phosphorylation at Ser78 include the Protein Kinase A (PKA) pathway [41]. PKA has been implicated in hypoxia-mediated EMT in lung cancer [42]. …”
Section: Discussionmentioning
confidence: 99%